Analysis of the Role of Zakat, Sadaqah, and Infaq in the Community Economy for Poverty Alleviation in Indonesia - Suprijati Sarib; Feb Amni Hayati; Sabil Mokodenseho; Siti Madina Lantong; Magfira Mamonto (Westscience Press, 2024)
This qualitative study delves into the role of Zakat, Sadaqah, and Infaq (ZSI) within the Indonesian community economy for poverty alleviation. Through interviews with diverse stakeholders, including representatives from Islamic charitable organizations, government officials, community leaders, and beneficiaries, as well as document analysis, the research explores perceptions, practices, impacts, challenges, and opportunities associated with ZSI initiatives. The findings reveal that ZSI plays a crucial role in providing social safety nets, fostering sustainable livelihoods, and promoting social cohesion within Indonesian communities. Despite governance issues and logistical challenges, collaborative partnerships, technology integration, and capacity building offer promising avenues for enhancing the effectiveness and sustainability of ZSI initiatives. Overall, this research underscores the significance of ZSI as a tool for promoting social justice, economic empowerment, and community resilience in Indonesia.